Implementasi Pembelajaran Teks Debat Berbantuan E-Modul di SMK Negeri 3 Yogyakarta: Kebijakan Pendidikan Abad 21 - Wulandari, Putri Ayu; Suhardi (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
21st century learning, including learning Indonesian requires students to think critically and creatively. The ministry's policy regarding text-based learning of Indonesian illustrates that currently learning Indonesian is not just at the level of remembering but has reached the level of creating. In line with this policy, this study aims to describe the implementation of e-module-assisted debate text learning at SMK Negeri 3 Yogyakarta. Descriptive research with a qualitative approach. A descriptive research design is used to describe the implementation of e-module assisted learning in debate texts in accordance with 21st century policies on the independent curriculum. The results of the study show that teaching debate texts using companion teaching materials such as e-modules is considered to be able to improve students' ability to think critically.